Association between comorbidity and participation in breast and cervical cancer screening: A systematic review and meta-analysis. (April 2017) - Diaz, Abbey; Kang, Jimin; Moore, Suzanne P; Baade, Peter; Langbecker, Danette; Condon, John R.; Valery, Patricia C.
Highlights: The design, measures and quality of included studies varied substantially. Low risk of bias studies found less cancer screening among women with comorbidity. The effect of specific chronic conditions needs investigation. Reasons for underscreening among women with comorbidity need to be explored. Abstract: Background: Comorbidity is associated with poor outcomes for cancer patients but it is less clear how it influences cancer prevention and early detection. This review synthesizes evidence from studies that have quantified the association between comorbidity and participation in breast and cervical screening. Methods: PubMed, CINAHL and EMBASE databases were systematically searched using key terms related to cancer screening and comorbidity for original research articles published between 1 January 1991 and 21 March 2016. Two reviewers independently screened 1283 studies that met eligibility criteria related to Population (adult, non-cancer populations), Exposure (comorbidity), Comparison (a 'no comorbidity' group), and Outcome (participation in breast cancer or cervical screening). Data was extracted and risk of bias assessed using a standardised tool from the 22 studies identified for inclusion (17 breast; 13 cervical). Meta-analyses were performed for participation in breast and cervical screening, stratified by important study characteristics. Results: The majority of studies were conducted in the United States. Results of individual studies were variable. Most had medium to high risk of bias. Based on the three "low risk of bias" studies, mammography screening was less common among those with comorbidity (pooled Odds Ratio 0.66, 95%CI 0.44–0.88). The one "low risk of bias" study of cervical screening reported a negative association between comorbidity and participation. Conclusion: While a definitive conclusion could not be drawn, the results from high quality studies suggest that women with comorbidity are less likely to participate in breast, and possibly cervical, cancer screening.